(untitled) (Plant Bulletin, 2025)
Optimizing seed rate plays a vital role in enhancing crop performance and productivity. Study was investigated with factors as two cultivars (PRI-NIAB Mung 2022 and PRI Mung 2018) and 4 seed rates (15, 20, 25 and 30 kg ha-1) were used in a randomized complete block design with factorial arrangement field experiment at the University of Agriculture, Faisalabad. The collected data showed that all growth and yield characteristics were strongly impacted by seed rate. More grain yield (1301.7 kg ha⁻¹), biological yield (8.35 t ha⁻¹), total dry matter (573.2 g m⁻²) and harvest index (18.14%) obtained under seed rate of 20 kg ha⁻¹. 25 kg ha⁻¹ produced the highest LAI (2.90), but 15 kg ha⁻¹ produced the most pods per plant (51.26), grains per pod (11.73), and 1000-grain weight (60.33 g). In most metrics, including RUE, PRI-NIAB Mung 2022 fared better than PRI Mung 2018. The study overall conclusion is that, given the agro climatic conditions of Faisalabad, 20 kg ha-1 with PRI-NIAB Mung 2022 is optimal for enhancing mung bean yield.